Scenarios for trade integration in the Americas - Diao, Xinshen; Díaz-Bonilla, Eugenio; Robinson, Sherman (CAIRN, 2003)
This paper analyzes two potential trade liberalization scenarios: a Free Trade Area of the Americas (FTAA) and an agreement between MERCOSUR and the European Union (EU). The paper utilizes a world general equilibrium model with some macro elements such as rigidities in wages and exchange rates. The empirical results show that the two regional integration scenarios create trade and increase welfare for the participants (more for the Latin American countries than for either the US or the EU) with little impact on non-participants. Realizing the potential benefits will also require adequate macroeconomic policies to avoid disruptive swings in trade balances.